Conhecendo as bactérias - Lopes , Cleuza Francisca da Silva; Lima, Maria dos Santos; Simião, Regina Aparecida Versoza; Guimarães , Renata Maria de Souza; Crescencio, Solange Paglarini (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf